Perbandingan Kinerja Kubernetes Cluster dengan Virtualisasi KVM, Vagrant dan LXD - Muhammad Arif Fadhly Ridha; Rahmat Suhatman (Politeknik Caltex Riau, 2022)
The development of technology that can package an application and its needs in a virtualization called a container, therefore we need a software that can manage containers, one of which is docker. However, the need is always increasing, the system is not able to accommodate many applications, therefore we need a software capable of managing clustering containers on a large scale. One such software is Kubernetes. Kubernetes can run in virtualization, virtualization that can run Kubernetes in it include vagrant, LXD and KVM. In this study, a comparison was made between the 3 types of virtualization, the comparison was made to see the success rate of high-availability, scalability and performance testing. The results of the research that was carried out when the Kubernetes cluster was implemented in Vagrant, LXD and KVM virtualization, it was found that KVM virtualization is superior to Vagrant and LXD virtualization, which can be seen from the large difference in latency and performance tests between the two virtualizations.